Poor things [videorecording (DVD)] - McNamara, Tony (Director); Stone, Emma, 1988-; Gray, Alasdair; Fendrix, Jerskin; Waddington, Holly; Ryan, Robbie; Ruffalo, Mark; Dafoe, Willem; Youssef, Ramy (20th Century Studios, 2024)
The tale and fantastical evolution of Bella Baxter, a young woman brought back to life by the brilliant and unorthodox scientist Dr. Godwin Baxter. Under Baxter's protection, Bella is eager to learn. Hungry for the worldliness she is lacking, Bella runs off with Duncan Wedderburn, a slick and debauched lawyer, on a whirlwind adventure across the continents. Free from the prejudices of her times, Bella grows steadfast in her purpose to stand for equality and liberation.